Effect of Water Content in the Gas Diffusion Layer of H2/O2 PEM Fuel Cell - Céspedes, Carlos Germán (2016)
The heart of a fuel cell is the membrane-electrode assembly consisting of two porous electrodes, where the electrochemical reactions take place, and the ionomer conductive membrane, which allows the proton exchange from the anode to the cathode. The porosity of the electrodes plays an important role in the fuel cell performance. One of the drawbacks presented by the porous electrodes is the accumulation of water in their structure, which implies a hindrance for the reactive gas transport to reach the catalytic reactive sites. In this paper, a mathematical model of a porous electrode, assuming single pores with uniform distribution, is introduced to determine the influence of water accumulation in the electrode on the fuel cell performance under different operating conditions. It is demonstrated that at low current densities, water accumulation has no effect in the fuel cell behavior, whereas at high current densities its performance is severely affected.